A review on potential adverse effects associated with Janus-kinase inhibitors - Kesavulu, Chennasamudram C.; P., Yashmeen Nikhat; Kumar, Jutla V.; Pooja, Mydukuru (International Journal of Basic & Clinical Pharmacology, 2024)
Rheumatoid arthritis (RA) is a chronic, symmetrical, inflammatory autoimmune disease that affects small joints. RA has a population prevalence of 0.5% to 1% in the U.S. The annual cost of care for chronic treatment of RA in the United States is estimated at $12,509. Pharmaceutical companies have developed drugs to treat RA using Janus kinase (JAK) inhibitors. These drugs can have potential adverse effects. Forecasting a better output to JAK inhibitors (JAKI’s). Therapy duration of JAKI’s and Problems regarding to strategies of dose reduction or if the discontinuation of therapy takes place in case of low disease activity. The accurate pharmacological profile and interactions of other drugs with JAKI’s have to establish. Proper safety, efficacy profile of JAKI’s and when administered in combination with DMARD’s. The safety, efficacy data of JAKI’s when compared to non-anti-TNF biologics. Obtaining of experience on JAKI’s that were already existed in the market and further experimental findings on newer compounds and which may clarify many of the aspects which are to be solved in nearer future as these JAKI will have greater application in treatment of RA. Regardless of significant developments in latest years in the pharmacotherapy of RA in the use of JAK inhibitors, yet the adverse effects of JAK inhibitors are unanswered. Therefore, one of the main concerns associated with JAK inhibitor is the potential adverse effects. The challenges can be addressed by clinical pharmacist mediated interventions related to dosing of JAK inhibitors and proper management of adverse drug reactions (ADRs).